GFRP for modified nano concrete flexual retrofitting of reinforced concrete beams - Brightson Poul Sebastin; Joe M Adams; Maria A Rajesh; Shalin Pricne (Sustainable Environment, 2023)
ABSTRACTThe structural behaviour of Glass Fibre Reinforced Polymer (GFRP) retrofitted reinforced concrete beam in addition with Nano admixtures (NA) was experimentally investigated and analysed. Globally, a large number of structures are subjected to unanticipated damages and deterioration. To renovate such buildings to serviceable state, repairing and retrofitting of damaged structures is the viable and economical option. This investigation aims to improve the resistance to flexure for reinforced beam by enhancing the mechanical properties concrete with the addition of various combinations of Nano admixtures (NA) as Nano silica (NS) and Nano clay (NC) and retrofitting the same. The void filling property of Nano admixtures produced a dense concrete with minimum voids in the concrete mass and improved the mechanical properties. To analyse the influence of Nano admixture, SEM analysis was done and the micro structure of the concrete mix was studied and analysed the microstructural features of the concrete. The structural mechanism of beams before and after wrapped with two layers of GFRP sheets was experimentally verified by this study.